LA GESTION DE LA DIVERSITE CULTURELLE PAR LES CHEFS D’ETABLISSEMENT REVUE DE LA LITTERATURE - Bauer, Stéphanie; Akkari, Abdeljalil (Revista Educação e Políticas em Debate, 2015)
Contemporary education systems need to address increasing Cultural diversity of students and the need to a change of perspective. From a problem to solve, cultural diversity can become an opportunity to improve learning. This article presents a synthesis of literature on the role of school principals in the management of cultural diversity. The academic literatureÂ Â on this issue is very heterogeneous. We present the main theoretical and conceptual debates. The notion of social justice appears to representÂ Â an innovative concept likely to destabilize unequal power relations between groups. The text discusses the professionalization of principals. This article highlights a tension between two visions of school leadership in the management of cultural diversity: a vision linked to critical pedagogy that develops multicultural education as a means to promote social justice and transformation of school structures. On the other side, an approach centered on management of education with a more focused approach towards measurable learning outcomesÂ Â and greater control of the cost of education.